Effects of particle size on mechanical and morphological properties of nano-magnesium hydroxide powder [Mg(OH)2] filled PP polymer composites - (:unkn) unknown (European Powder Metallurgy Association (EPMA), 2011)
Polymer matrix nanocomposites have attracted considerable academic and industrial interest because nanoscale effects have the potential to afford significant improvements in properties such as impact resistance, modulus, thermal stability and fire resistance compared with those of pure polymers. In addition, Polymers are often filled with particulate fillers in order to improve the barrier properties of the neat polymer or reduce the cost of the final product. In this study, three kinds of Mg(OH)2, with different particle sizes and ratios, were chosen to investigate the influence of particle sizes and ratios on the mechanical, thermal and morphological properties of polypropylene (PP) composites. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM), Differential scanning calorimeter (DSC) and Energy dispersive X-ray spectroscopy (EDS). Furthermore, PP composites were subjected to examinations to obtain their tensile strengths, yield strengths, elasticity modulus, percent elongation, Izod impact strength and hardness.
Keywords: Magnesium hydroxide; Nanocomposites; Particle size; Polypropylene